Hubungan Pelayanan Kebidanan yang Service Excellent dengan Kepuasan Pasien diPuskesmas Pintu Pohan Meranti Kabupaten Toba - Naibaho, Febrianti; Surbakti, Imran; Simanjuntak, Parningotan (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
Excellent service is a concern for customers by providing the best service tofacilitate fulfillment of their needs and fulfillment of their satisfaction so that they are always loyal. Health services provided to patients cannot be separated from midwifery services. Midwifery services play an important role in healing disease and restoring health. Purpose: This study aims to determine the relationship between the midwifery services provided very well with the level of patient satisfaction at the Pintu Pohan Meranti Health Center in 2020. Method: This type of research is an analytic observational study with a crosssectional approach. The sample in this study were 46 patients who came andreceived midwifery services at the Pintu Pohan Meranti Health Center in 2020.The data analysis technique used chi square. Results: obtained in this studywere 46 respondents who felt more satisfied with patients who receive midwifery services 27 people (87.1%) had excellent service compared to 3patients who did not get midwifery services (20.0%). The proportion of patients who were dissatisfied was more in patients who did not receive midwifery service with prime service 12 people (80.0%) compared to patients whoreceived midwifery service with excellent service 4 people (12.9%). Conclusion:There is a significant relationship between excellent service midwifery service and patient satisfaction at the Pintu Pohan Meranti Health Center. It is hopethat the Puskesmas will also conduct regular evaluation of midwifery servicesso that they can continue to monitor the quality of midwifery servicesperformed.